The non-existence of equilibrium in sequential auctions when bids are revealed. - Cai, Gangshu; Wurman, Peter R.; Chao, Xiuli (My University, 2011)
Sequential auctions of homogeneous objects are common in public and private marketplaces. Weber derived equilibrium results for what is now a classic model of sequential auctions. However, Weber’s results are derived in the context of two particular price quote assumptions. In this paper, we examine a model of sequential auctions based on online auctions, in which, after each auction, all bids are revealed. We show that a pure-strategic, symmetric equilibrium does not exist, regardless of whether the auctions are first- or second-price, if all bids are revealed at the end of each auction.
Keywords: Sequential auctions; Online auctions; E-commerce; Nash equilibrium